Une sociologie des usages des TIC à l'épreuve du temps libre : le cas des lycéens durant l'année du baccalauréat - Laurence Le Douarin (Nantes Université, 2014)
What's sociological though to understand the use of ICT by students of final year? It says that they are the "Google generation" which raises problems (literacy, internet risks, etc.). We would understand their digital uses for homework, by studying the social contexts of use and how they articulate school work and leisure.